2018
DOI: 10.1161/strokeaha.118.022280
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Cortical Microinfarcts on Magnetic Resonance Imaging and Their Association With Cognition in Cerebral Amyloid Angiopathy

Abstract: Background and Purpose: We aimed to explore the association between presence of cerebral cortical microinfarcts (CMIs) on MRI and other small vessel disease neuroimaging biomarkers in cerebral amyloid angiopathy (CAA) and to analyze the role of CMIs on individual cognitive domains and dementia conversion. Methods: Participants were recruited from an ongoing longitudinal research cohort of eligible CAA patients between March 2006 and October 2016. A total of 102 cases were included in the analysis that assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 37 publications
3
45
1
Order By: Relevance
“…Therefore, the modification of this system produces deleterious effects, whose results are an accumulation of catabolites and toxic substances, together with a great impoverishment of neural nutrition [357][358][359]. The enlargement and widening of PVS, lead a consequent leakage of fluid and plasma cells due to an obstructive process maintained by catabolites, proteins, and cell debris [35], together with the disruption of the BBB, which might eventually potentiate the perivascular inflammation, and all of the cascades of the inflammatory/obstructive/stagnation-induced process [360][361][362]. Therefore, many Authors have tried to propose a biochemical profile of SVD, in order to better evaluate and support the radiological progressions of the SVD and its clinical monitoring [320,[363][364][365][366] Low et al [367] systematically reviewed the existing literature on the associations between markers of inflammation and SVD in cohorts of older people with good health, cerebrovascular disease, or cognitive impairment.…”
Section: Svd: Inflammation As a Promoter Or A Markermentioning
confidence: 99%
“…Therefore, the modification of this system produces deleterious effects, whose results are an accumulation of catabolites and toxic substances, together with a great impoverishment of neural nutrition [357][358][359]. The enlargement and widening of PVS, lead a consequent leakage of fluid and plasma cells due to an obstructive process maintained by catabolites, proteins, and cell debris [35], together with the disruption of the BBB, which might eventually potentiate the perivascular inflammation, and all of the cascades of the inflammatory/obstructive/stagnation-induced process [360][361][362]. Therefore, many Authors have tried to propose a biochemical profile of SVD, in order to better evaluate and support the radiological progressions of the SVD and its clinical monitoring [320,[363][364][365][366] Low et al [367] systematically reviewed the existing literature on the associations between markers of inflammation and SVD in cohorts of older people with good health, cerebrovascular disease, or cognitive impairment.…”
Section: Svd: Inflammation As a Promoter Or A Markermentioning
confidence: 99%
“…We found six studies in which links between brain volume or atrophy and various MRI markers were tested. 36,[47][48][49][50][51] These markers comprise MB in two studies, diffusion tensor imaging metrics in one, perivascular spaces in one and cortical microinfarcts in two.…”
Section: Longitudinal Datamentioning
confidence: 99%
“…57,58 In the study in CAA, the brain volume was calculated by multiplying by 2 that of the non-hemorrhagic hemisphere. 51 Three of the four studies in CADASIL reported significant associations between brain atrophy and cognitive worsening during follow-up. Surprisingly however, the fourth study reported a significant association between ventricular enlargement and cognitive worsening, which strongly questions the method to measure brain atrophy.…”
Section: Longitudinal Datamentioning
confidence: 99%
“…However, independent of AD, clinically CAA is a significant contributor to vascular-mediated cognitive impairment and dementia (VCID) [3,4,7]. As a prominent small vessel disease CAA contributes to the cognitive decline in VCID in several ways by promoting perivascular neuroinflammation, impaired cerebral blood flow and ischemic infarcts, cerebral microbleeds, and larger hemorrhages, all of which can result in neuronal dysfunction, neuronal loss and white matter damage [3,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%